Blood Reference Intervals for Antillean Manatees (Trichechus manatus manatus) from Puerto Rico - Antonio A. Mignucci-Giannoni; Mayela M. Alsina-Guerrero (Veterinary Medicine International)
Antillean manatees (Trichechus manatus manatus) are endangered throughout the southwestern Gulf of Mexico, the Caribbean coast of Central and South America, the Greater Antilles, and the northeastern coast of South America to Brazil. Establishing blood reference intervals is essential as a tool in classifying health status, diagnosing, establishing treatment regimens, and monitoring the progress of a disease in rescued manatees. We collected blood samples from 44 free-ranging and 26 rescued manatees from Puerto Rico between 1992 and 2020 for hematology and blood chemistry analysis. We obtained values for white blood cell count and red blood cell count, hemoglobin, hematocrit, platelet, mean cell volume, mean cell hemoglobin, mean cell hemoglobin concentration, and red cell distribution width. A manual leukocyte differential allowed for the evaluation of different cell types. In addition, we performed a comprehensive metabolic panel on serum samples. These analytes were grouped based on six physiologic processes: liver-associated enzymes and pigments; muscle-associated enzymes; kidney-associated compounds and products; sugars, lipids, and pancreatic-associated enzymes; proteins; and electrolytes. For every parameter, summary statistics of values were calculated on all the samples. Reference ranges were determined as ±1 standard deviation around the mean. An unpaired two-sample T-test was done comparing males versus females and adults versus calves for any significant differences (p≤0.05). We establish the reference intervals of hematology and blood chemistry for the population of Antillean manatees in Puerto Rico and compare them with those established for manatees from Belize, Brazil, Florida, Guyana, and Mexico.